Pengaruh Pemasaran Internal terhadap Kualitas Pelayanan, Kepuasan Pelanggan dan Loyalitas Pelanggan pada Perguruan Tinggi Swasta (PTS) di Jawa Timur - Sukotjo, Hendri (Universitas Brawijaya, Indonesia, 2012)
Internal marketing that properly done would have an impact on service quality, which furthercould increase customer satisfaction and customer loyalty. The purpose of this research was to determinethe effect of internal marketing on service quality, customer satisfaction, and customer loyalty on privateuniversity in East Java. The result of this research shows that: 1. Internal marketing has not been abledirectly to increase service quality and customer satisfaction, 2. Internal marketing could directly increasecustomer loyalty. But, when connected undirectly through intervening variable of service quality andcustomer satisfaction, the total effect would be negative. This result shows that internal marketing could bea booster to customer loyalty, but the impact of this boost factor depend on service quality factor whichreceived by customer, and by customer satisfaction factor.